News librarians and social networks - Guallar, Javier (Anuario ThinkEPI, 2012)
The importance of social networks for mass media professionals, especially for news librarians -whose traditional intermediary role limited their visibility to users- is explained. Examples of documentation centres and news librarians´ profiles in social media like weblogs, Facebook, Twitter or Eskup are offered.